Ion Transport Induced by Polycations and its Relationship to Loose Coupling of Corn Mitochondria - Hanson, J. B. (1972)
Treatment of corn mitochondria (Zea mays L., WF9 (Tms) × M14) with polycations (protamine, pancreatic ribonuclease, or polylysine) releases acceptorless respiration if phosphate is present. Concurrently, there is extensive active swelling which is reversed when respiration is uncoupled or stopped. Mersalyl, the phosphate transport inhibitor, blocks both the release of respiration and the active swelling. Diversion of energy into phosphate transport lowers respiratory control and ADP: O ratios. This response is termed “loose coupling” in distinction to “uncoupling” in which energy is made unavailable for either transport or ATP formation. Corn mitochondria as used here are endogenously loose coupled to some extent, and show state 4 respiration linked to active transport. The action of polycations can be partially mimicked by lowering pH of the suspending medium; both give swelling in sucrose medium and increased light absorbancy. Triton X-100, a nonionic detergent, will uncouple and accentuate active swelling, but unlike polycations it will not release state 4 respiration. Calcium ion acts something like polycation in activating phosphate transport and releasing respiration, and polycation appears to block entry of Ca(2+). It is speculated that neutralization of certain negatively charged acid groups on the membranes by polycations increases permeability to solutes and decreases coulombic repulsion of phosphate in approaching transport sites. In consequence, respiration rates and active transport rates increase.